The mathematical proficiency of the students of the mathematics department - Jasim, Noor M.; Faris, Ilham J. (Opción, 2019)
To achieve the objective of the research to identify the mathematical proficiency of the students of the Department of Mathematics in the faculties of education, a test was constructed measuring cognitive mathematical proficiency (conceptual understanding, procedural fluency, strategic efficiency, adaptive reasoning) of (37) paragraphs. The results showed the skill of the students of the research sample in some of its components which is the adaptive inference and the inclination produced and they are not proficient in conceptual understanding, procedural fluency and strategic efficiency. In conclusion, students of the Department of Mathematics in Education Colleges are proficient in mathematics.